Study the effects of naturally acquired canine Dirofil Ariasis on some hematological and biochemical parameters: Amal Hassen Atyha and Donia A.A. Alani - Atyha, Amal Hassen (The Iraqi Journal of Veterinary Medicine, 2017)
The present study was aimed to check the amount of variation in some hematologic and biochemical parameters accompanied with natural acquired canine dirofilariasis. Blood samples were collected from sixty five stray dogs (5-10) years old belong to local breed dog in the villages of Al-Hindya area/ Karbala Governorate, The affected animal showed differences in hematological and biochemical values as compared with reference ranges. In conclusion, the disease showed no significant clinical signs although many pathological changes in some blood constituent with serum biochemical parameters were observed, before euthanasia for dogs.